section3_6

# section3_6 - Section 3.6 Sum Difference Product Quotient...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Section 3.6 Sum, Difference, Product, Quotient, and Composition of Functions Page 1 of 14 Example 1: For the functions f ( x) = 2 x 2 − 4 x + 1 and g ( x) = 7 x, find f + g , f − g , fg , and their domains. Solution to Example 1: f , g Section 3.6 Sum, Difference, Product, Quotient, and Composition of Functions Page 2 of 14 Example 2: For the functions f ( x) = 3 x + 1 and g ( x) = 4 x + 5, find ( f + g ) (1), ( f − g ) (2), f (−2), and ( f g ) (3). g Solution to Example 2: ( fg ) (−1), Section 3.6 Sum, Difference, Product, Quotient, and Composition of Functions Page 3 of 14 Example 3: For the functions f ( x) = x 2 − 5 and g ( x) = x3 + 1, find f g , g f , and their domains. Solution to Example 3: Section 3.6 Sum, Difference, Product, Quotient, and Composition of Functions Page 4 of 14 Example 4: Solution to Example 4: Section 3.6 Sum, Difference, Product, Quotient, and Composition of Functions Page 5 of 14 Section 3.6 Sum, Difference, Product, Quotient, and Composition of Functions Page 6 of 14 Example 5: Solution to Example 5: Section 3.6 Sum, Difference, Product, Quotient, and Composition of Functions Page 7 of 14 Example 6: Solution to Example 6: Section 3.6 Sum, Difference, Product, Quotient, and Composition of Functions Page 8 of 14 Section 3.6 Sum, Difference, Product, Quotient, and Composition of Functions Page 9 of 14 Example 7: Solution to Example 7: Section 3.6 Sum, Difference, Product, Quotient, and Composition of Functions Page 10 of 14 Example 8: Solution to Example 8: Section 3.6 Sum, Difference, Product, Quotient, and Composition of Functions Page 11 of 14 Exercise Set 3.6: Combining Functions Answer the following. 1. f 8 6 4 2 −6 −4 −2 2 4 6 x 8 y For each of the following problems: (a) Find f + g and its domain. g (b) Find f − g and its domain. (c) Find fg and its domain. (d) Find f and its domain. g Note for (a)-(d): Do not sketch any graphs. 3. 4. 5. f ( x ) = 2 x + 3; g ( x ) = x 2 − 4 x − 12 f ( x ) = 2 x3 − 5 x; g ( x) = x 2 + 8 x + 15 −2 −4 −6 (a) Find f (−3) + g (−3) . (b) Find f (0) + g (0) . (c) Find f (−6) + g (−6) . (d) Find f (5) + g (5) . (e) Find f (7) + g (7) . (f) Sketch the graph of f + g . (Hint: For any x value, add the y values of f and g.) (g) What is the domain of f + g ? Explain how you obtained your answer. 2. f y f ( x) = 3 x ; g ( x) = x+2 x −1 2x 4 ; g ( x) = x−5 x−5 6. 7. 8. 9. f ( x) = f ( x ) = x − 6 ; g ( x ) = 10 − x f ( x) = 2 x − 3 ; g ( x) = x + 4 f ( x) = x 2 − 9 ; g ( x) = x 2 + 4 8 6 4 2 −6 −4 −2 10. f ( x) = 49 − x 2 ; g ( x) = x − 3 g Find the domain of each of the following functions. x 2 4 6 8 11. f ( x) = 2 + x −1 x −3 3 x −2 −4 −6 12. h( x) = x + 2 − (a) Find f (−2) − g (−2) . (b) Find f (0) − g (0) . (c) Find f (−4) − g (−4) . (d) Find f (2) − g (2) . (e) Find f (4) − g (4) . (f) Sketch the graph of f − g . (Hint: For any x value, subtract the y values of f and g.) (g) What is the domain of f − g ? Explain how you obtained your answer. 13. g ( x) = 3 x +1 − x−7 x−2 5 x−2 + +7 x + 6 x −1 14. f ( x) = 15. f ( x) = x+2 x −5 x−3 x −1 16. g ( x) = Exercise Set 3.6: Combining Functions Answer the following, using the graph below. 8 y For each of the following problems: (a) Find f g and its domain. (b) Find g f and its domain. 33. f ( x) = x 2 + 3x; g ( x) = 2 x − 7 f 6 4 2 g x 2 4 6 8 34. f ( x) = 6 x + 2; g ( x) = 7 − x 2 35. f ( x) = x 2 ; g ( x) = 3 x+5 1 x−4 −6 −4 −2 −2 −4 −6 17. (a) g (2) (c) f ( 2) 18. (a) g (0) (c) f (0) 19. (a) 20. (a) 21. (a) 22. (a) 23. (a) 24. (a) (b) f (g (2)) (d) g ( f (2)) (b) f (g (0)) (d) g ( f (0)) (b) (b) (b) (b) (b) (b) 36. f ( x) = ; g ( x) = x 2 37. f ( x) = x + 7 ; g ( x) = −5 − x 38. f ( x) = 3 − x ; g ( x) = 9 − 2 x (f (f g )(− 3) g )(− 1) f )(3) f )(5) g )(4 ) g )(− 5) (g (g f )(− 3) f )(− 1) g )(− 2 ) g )(− 3) f )(4 ) g )(2 ) Answer the following. 39. Given the functions f ( x) = x 2 + 2 and g ( x) = 5 x − 8 , find: (a) (c) (e) (g) f (g (1)) f (g (x )) f ( f (1)) f ( f (x )) (f (f (f (g (g (g (f (f (b) (d) (f) (h) g ( f (1)) g ( f (x )) g (g (1)) g (g (x )) Use the functions f and g given below to evaluate the following expressions: f ( x) = 3 − 2 x and g ( x) = x 2 − 5 x + 4 40. Given the functions f ( x) = x + 1 and g ( x) = 3 x − 2 x 2 , find: 25. (a) g (0) (c) f (0) 26. (a) g (−1) (c) f (−1) 27. (a) 28. (a) 29. (a) 30. (a) 31. (a) 32. (a) (b) f (g (0)) (d) g ( f (0)) (b) f (g (− 1)) (d) g ( f (− 1)) (b) (b) (b) (b) (b) (b) (a) (c) (e) (g) f (g (− 3)) f (g (x )) f ( f (− 3)) f ( f (x )) (b) (d) (f) (h) g ( f (− 3)) g ( f (x )) g (g (− 3)) g (g (x )) x +1 and x−2 41. Given the functions f ( x) = g ( x) = 3 , find: x−5 (f g )(− 2) g )(4 ) f )(6) f )(− 4 ) g )(x ) f )(x ) (g f )(− 2) f )(4 ) g )(6) g )(− 4 ) f )(x ) g )(x ) (f (f (f (f (f (g (g (g (g (g (a) f (g (− 2)) (c) f (g (x )) (b) g ( f (− 2)) (d) g ( f (x )) 2x and x+5 42. Given the functions f ( x) = g ( x) = 7−x , find: x −1 (a) f (g (3)) (c) f (g (x )) (b) g ( f (3)) (d) g ( f (x )) Exercise Set 3.6: Combining Functions 43. Given the functions f ( x ) = x 2 − 1, g ( x) = 3x − 5, and h( x) = 1 − 2 x, find: (a) f (g (h(2))) (c) f g h 44. Given the functions (b) g (h( f (3))) (d) g h f f ( x) = 2 x 2 + 3, g ( x) = x + 4, and h( x) = 3 x − 2, find: (a) f (g (h(1))) (c) f g h 45. Given the functions (b) g (h( f (1))) (d) g h f f ( x ) = x 2 + 4, g ( x) = x + 3 , and h( x ) = 2 x + 1, find: (a) h( f (g (4))) (c) f g h 46. Given the functions f ( x) = 1 x2 (b) f (g (h(0))) (d) h f g , g ( x) = x − 2 , and h( x) = 3 − 4 x, find: (a) h( f (g (5))) (c) f g h (b) f (g (h(− 2))) (d) h f g ...
View Full Document

## This document was uploaded on 07/14/2010.

Ask a homework question - tutors are online